Environmental Protection Through Sustainable Land Management - Rahim Foroughi; Farhad Daneshgar (Environmental Science and Sustainable Development)
Sustainable land planning and successful land use change methods are essential as the world faces rising environmental challenges. This study examines the transformative potential of biomimicry and biophilia in addressing these challenges and the potential of bio-collaboration, bio-utilization, bio-inspiration, biophilic design, and biomimicry in creating a sustainable environment. The argument is that such integration can potentially create creative ways to lessen the effects of human activity on the environment by utilising the knowledge of nature and combining biological system concepts. This study argues that by incorporating the above environmental factors into land planning practises, a holistic and sustainable approach can be achieved, fostering peaceful coexistence between human activities and the natural environment. This will also improve the resilience of urban and rural environments while offering practical solutions for a climate change-conscious world. As the main theoretical contribution, this study synthesizes a theoretical framework in the form of a conceptual structure for understanding, analyzing, and interpreting sustainability by adopting an ecosystem theoretical framework for achieving sustainable land management.